Navigational system analysis using image processing for visually impaired - Chakravorty, Naireet; Afroz, Nazia; Gupta, Dipayan Sen (BRAC University, 2016)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2016.